2013
DOI: 10.1186/2193-1801-2-397
|View full text |Cite
|
Sign up to set email alerts
|

Individual quality of life in patients with multiple myeloma

Abstract: ObjectiveThe situation of patients with multiple myeloma, whose treatment often implies high-dose chemotherapy and stem cell transplantation that can be associated with severe symptoms and psychological distress, has gained attention in recent psychooncological research. This study followed an idiographic approach in order to identify the areas of life most relevant for the interviewed myeloma patients’ quality of life (QoL) as well as their current satisfaction with these.Methods64 patients took part in semi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…In particular, the treatment of haemato-oncological diseases, such as lymphoma, often implies high-dose chemotherapy, which can be associated with severe symptoms and psychological distress creating difficulties in fulfilling family and social roles (e.g. be able to work or participating in daily social activities) and having a major impact in patient QoL [5]. Despite there is no consensus in the literature, QoL term is seen as a multidimensional (physical, psychological, social, and spiritual), subjective, and dynamic concept [1].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the treatment of haemato-oncological diseases, such as lymphoma, often implies high-dose chemotherapy, which can be associated with severe symptoms and psychological distress creating difficulties in fulfilling family and social roles (e.g. be able to work or participating in daily social activities) and having a major impact in patient QoL [5]. Despite there is no consensus in the literature, QoL term is seen as a multidimensional (physical, psychological, social, and spiritual), subjective, and dynamic concept [1].…”
Section: Introductionmentioning
confidence: 99%
“…In general, research indicates a consensual positive association between perceived support by family, friends and community and patients’ QoL (Wang et al, 2015). The personal social relationships are also reported as a relevant aspect in MM patients’ QoL (Dürner et al, 2013). High levels of perceived social support have been associated with a decrease in psychological morbidity (Rini et al, 2016), such as anxiety and depression and an increase in QoL (Molassiotis et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Al-Natour et al, 2017). Higher levels of spirituality not only are associated with better QoL (Barata et al, 2016; Bovero et al, 2015; Dürner et al, 2013; Slovacek et al, 2007), but also with a decrease in physical symptoms and lower anxiety and depression levels (Barata et al, 2016; Slovacek et al, 2007). Therefore, spirituality can be a predictor of QoL (Sirilla and Overcash, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Family support and social relationships contribute to higher levels of QoL, assuming an important buffer over the impact of stress (Molassiotis et al, ). A study with patients with MM showed that social relationships were considered more important for QoL than aspects related to their health (Dürner, Reinecker, & Csef, ). In the QoL's model of Wilson and Cleary () adapted to patients with MM, social support is crucial, impacting directly on QoL.…”
Section: Discussionmentioning
confidence: 99%